Memories of cinemagoing and film experience: An introduction. (January 2017) - Kuhn, Annette; Biltereyst, Daniel; Meers, Philippe
Over the past two decades, the relationship between cinema and memory has been the object of increasing academic attention, with growing interest in film and cinema as repositories for representing, shaping, (re)creating or indexing forms of individual and collective memory. This Special Issue on memory and the experience of cinemagoing centres on the perspective of cinema users and audiences, focusing on memories of films, cinema and cinemagoing from three continents and over five decades of the twentieth century. This introduction considers the relationship between memory studies and film studies, sets out an overview of the origins of, and recent and current shifts and trends within, research and scholarship at the interface between historical film audiences, the cinemagoing experience and memory; and presents the articles and reviews which follow within this frame. It considers some of the methodological issues raised by research in these areas and concludes by looking at some of the challenges facing future work in the field.